Study and analyse the role of branding of tourist attractions in the sustainable development of tourism (The Peerian Journal, 2024)
The tourism sector is considered a leading industry in the world, and despite the remarkable development this sector has witnessed, it has significant impacts on different countries. The status of a tourist destination can be improved by paying attention to its development standards, and at the same time, branding plays a vital role in tourism growth. Tourism destination branding includes activities and programs that distinguish the destination and enhance the emotional connection between the tourist and the destination. This study aims to examine the impact of tourism standards from the citizens' point of view and determine the tourism brand of the city of Muthanna from the elites' point of view. The research is applied and uses a descriptive and analytical approach. Data were collected through two documentary methods and a survey with a statistical community of 30 experts in the field of tourism. The impact of tourism standards on people's opinions was also analyzed using SPSS software and a statistical sample of 384 people. The city of Al-Muthanna, with an area of 51,740 square kilometres, was identified as the research area. The research results showed that the tourism situation in Muthanna could be better and acceptable and that tourism experts prioritize indicators of well-being, safety, hospitality, and the standard of luxury. The accommodations were chosen to be the tourist brand of Al-Muthanna City.